Outcome prediction of sepsis-induced acute kidney injury by plasma endostatin: prospective observational study - Farouk Mostafa Faris; Mahmoud Mostafa; Rania Mostafa Elhoseiny; Walid Omar Ahmed (Egyptian Journal of Critical Care Medicine)
Abstract Introduction Approximately 50% of patients in intensive care units (ICU), particularly those with sepsis develop acute kidney injury (AKI). Plasma endostatin, which is released from the basement membrane of Bowman’s capsule, increases early during AKI. Aim of work To evaluate the predictive value of plasma endostatin for renal recovery and its correlation with ICU stay and mortality in sepsis-induced AKI in patients admitted to the ICU. Methods An observational, prospective single-centre study was conducted on 40 septic patients at the Critical Care Department of Cairo University hospitals. The patients were divided according to AKI occurrence and renal recovery. Plasma endostatin levels were measured for 3 times at the day of admission, after 48 h and after 96 h. APACHE II and SOFA scores were computed, and forced diuresis was administered as indicated. Results Forty patients with a mean age of 60.7 ± 17.8 and 47.5% males were included in the study. Total 28-day mortality was 42.5% (13% in the sepsis without AKI group, 37.5% in the recovered AKI group, and 100% in the group without renal recovery). The endostatin level on day 0 was significantly higher in the recovery group compared to the non-recovery group (P-value = 0.014). Gradual decrease of plasma endostatin level is associated with decrease of creatinine level in recovery group (weak positive correlation r = 0.3, P = 0.05). The cut-off value of plasma endostatin at the day of admission for predicting recovery is 180 ng/dl, with a specificity of 88.9% and a sensitivity of 81.9%. Conclusion Higher levels of plasma endostatin at the onset of septic AKI predict renal recovery and the success of forced diuresis. Acute kidney injury increases mortality rates, particularly if recovery is not achieved.